Chronic consumption of a healthy diet interacts with the clock gene locus to modify glucose metabolism among metabolic syndrome patients from the CORDIOPREV intervention study (2013)
Introduction: Circadian Locomotor Output Cycles Kaput (CLOCK) gene has been related with lifestyle-related diseases such as obesity, metabolic syndrome (MetS), and cardiovascular diseases. Hypothesis: We assessed wheter the chronic consumption of a Mediterranean diet enriched in olive oil, compared with a Low fat diet, interacts with three common single nucleotide polymorphisms (SNPs) at CLOCK locus (rs1801260, rs3749474, and rs4580704) in order to improve glucose metabolism among MetS patients. Methods: Index related with glucose metabolism ((the homeostasis model assessment of insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI)), insulin concentrations, and CLOCK SNPs were determined in 581 MetS subjects from the CORDIOPREV clinical trial (NCT00924937). Gene-diet interactions were analysed after one year of dietary treatment (Mediterranean diet (38% fat, 22% MUFA) vs Low fat diet (<28% fat, 12% MUFA)). Results: We found a gene-diet interaction between rs1801260 SNP and dietary pattern for insulin concentrations (P=0.009), HOMA-IR (P=0.014) and QUICKI (P=0.028). Specifically, after 12 months of Low fat intervention, homozygous for the major allele (AA) displayed lower plasma insulin concentrations (P=0.032), lower insulin resistance (HOMA-IR; P=0.027) and higher sensibility of insulin (QUICKI index; P=0.024) compared with carriers of the minor allele G (AG+GG). No other gene-diet interactions were found. Conclusions: Chronic consumption of a healthy diet may play a contributing role in triggering glucose metabolism by interacting with the rs1801260 SNP at CLOCK gene locus in MetS patients. Due to the complex nature of gene-environment interactions, dietary adjustment in subject with the MetS may require a personalized approach.